ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DAN PENGUPAHAN SECARA EFEKTIF DAN EFISIEN PADA RUMAH SAKIT UMUM DAERAH TARUTUNG - LUNA THERESIA TAMBUNAN (JURNAL ILMIAH MAKSITEK, 2020)
In this study, honorary employees received salaries, but there were honorary employees who received wages, such asambulance coordinators and ambulance drivers. They get a reward when there are patients who need an ambulance, andthe coordinator also gets a reward for being tasked with coordinating the use of the ambulance car. All matters relating tosalary and wages shall be supported by forms, records or other supporting evidence in accordance with generally applicableregulations, or regulations made and applicable within the company. Researchers have also conducted preliminary researchand obtained general data on how the process of Payroll and Wage Accounting Information System in Tarutung RegionalGeneral Hospital. The procedure begins with the making of the payroll and wages by the administration, then the payroll andwages are sent to the finance department and then the finance department sends the payroll to the bank and the financedepartment sends the salary to the honorary employees, while for the wages will be directly given to the recipient through anintermediary. Then the finance department will issue cash outgoing evidence that will be used as a basic proof of salary andwage payments to hospital employees. Payroll and Wage Accounting Information System in Tarutung Regional GeneralHospital has not run effectively and efficiently, which has not been effective, because sometimes there are still employeeswho do activities about payroll and wages manually, such as in the process of wages, although there are procedures butsometimes the provision of wages is done manually, because when making wage payments manually, employees consider iteasier and easier to realize than following existing procedures , because wages are rare in this hospital.